Characterizing T-cell receptor ?-variable gene in Aotus nancymaae owl monkey peripheral blood (2003)
Abstract: ?? T lymphocytes have a heterodimeric complex formed by the association of ? and ? chains as receptor. Proliferation of this lymphocyte population has been observed, when infection by several pathogens such as Mycobacterium tuberculosis and Plasmodium spp. occurs. The New World Monkey Aotus nancymaae has become a very good experimental model for the immunological and physiopathological study of these infectious agents. The A. nancymaae ??variable region was characterized from peripheral blood samples by using cDNA and genomic DNA polymerase chain reaction amplification, DNA sequencing, and dot?blot hybridization techniques. Seventeen different T?cell receptor ??variable (TCRGV) sequences were obtained. These sequences were distributed among TCRGV subsets 1, 2, or 3, according to human subset classification. Although no subset 4 amplification was obtained, this subset was detected by dot?blot hybridization. The presence of these 4 subsets resembles the behavior displayed by ‘???low species’ (humans and mice), where high diversity among these lymphocytes can be observed. Homologies greater than 70% were found with respect to humans. Sequence convergence between human and A. nancymaae subsets 1 and 3 highlights Aotus as a promising model for studying these lymphocyte functions.